Philippine libraries and librarianship, 1900-2000 a historical perspective - Perez, R Dante O.; Faderon, Rosalie B.; Vallejo, Rosa M.; Picache, Ursula G. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study was conducted to determine the people, places and events that contributed to the history of Philippine libraries and librarianship, thereby producing an updated, definitive and comprehensive Philippine library history. It also corrected some erroneous and inaccurate data that were published in many sources and accepted as part of library history. Documentary sources found in library schools, libraries, archives, library associations, and public and private institutions were examined. Personal interviews of librarians, both active and retired, library school administrators, personnel and staff of libraries and archives, and retired library educators throughout the country were made to review data that were not adequately documented or verified. Since Vicente S. Hernandez's A History of Books and Libraries in the Philippines, 1521-1900, ended at 1900, this study starts from the establishment of the American Circulating Library on March 9, 1900 up to the end of the year 2000.
This study covers the beginning of the modern public library movement and the first government library and the library legislations that defined their functions, structure and legal status in the early years from 1901 to 1916; the education of librarians from 1914 to 2000; the pioneering work of the University of the Philippines Institute of Library Science in the introduction of information technology in the library and information science curriculum; the organizations of librarians from 1923 to 2000; the professionalization of librarians with the passage of Republic Act No. 6966, also known as "The Philippine Librarianship Act" in 1990; and the library buildings constructed from 1931 to 2000.
The findings of the study show that the modern public library movement started 1900 with establishment of the American Circulating Library and its eventual donation to the Philippine government in 1901. Through a series of library legislation, the American Circulating Library became the Philippine Library in 1909, the Philippine Library and Museum in 1916, the National Library in 1928, the Bureau of Public Libraries in 1947 and finally the National Library in 1964. The first government libraries are the Bureau of Science, the National Archives and the Military Information Division. Likewise, they were all created by laws.
The study identified the 101 schools that provided the formal training of librarians through the 14 undergraduate and 12 graduate programs from 1914 to 2000. The University of the Philippines Institute of Library Science pioneered in the introduction of information technology in the library and information science curriculum that led to the UNESCO-sponsored Post-Graduate Training Course for Science Information Specialists in Southeast Asia from 1978 to 1984. There were 61 library associations from 1923 to 2000, majority of which were formed in the 1970's. The seven groups of library associations consist of 9 national library associations, 10 regional library associations, 17 provincial library associations, 9 local library associations, 5 library science alumni associations, 5 student library associations and 6 library-related associations. Nineteen library associations are no longer in existence.
The professionalization of librarians was achieved with the passage of Republic Act No. 6966 on September 19, 1990 after twenty-two years of struggle. Before this, a series of civil service examinations was conducted by the Bureau of Civil Service and the Civil Service Commission to allow librarians to work in government libraries. Librarians are now licensed by the Professional Regulation Commission to practice the profession. Eighty-three library buildings were constructed from 1931-2000, of which 41 are academic libraries, 30 are public libraries, 8 are school libraries and 4 are special libraries, with structure varying from one storey to six storeys.
There are ten erroneous data pertaining to the official date of when the first courses were offered at the University of the Philippines, University of Santo Tomas, the Centro Escolar University and the Philippine Women's University; date of foundation of the Philippine Library Association, the Association of Special Libraries of the Philippines, the Philippine Association of Academic and Research Libraries and the Medical and Health Library Association, the date when "Public Library Day" was first observed, and who signed Executive Order No. 94 which created the Bureau of Public Libraries.
The study concluded that the American colonizers started the modern public library movement in the Philippines with the establishment of the American circulating Library on March 9, 1900 that led to the creation of The National Library in 1964. The growth of Philippine libraries and librarianship from 1900 to 1990 was greatly enhanced by laws passed for various library matters that gave libraries a solid foundation. Laws greatly influenced libraries and librarianship even up to 1990 with the passage of Republic Act No 6966 known as "The Philippine Librarianship Act" which regulated the practice of librarianship in the country. The rapid growth of libraries and librarianship after World War II resulted in the establishment of many library schools to provide the necessary trained manpower, the formation of library associations, the professionalization of librarians, the construction of library buildings and integration of information technology in the curriculum of library schools, in around 50 years. Not much literature on Philippine libraries written by Vicente S. Hernandez, A History of Books and Libraries in the Philippines, 1521-1900, which traces the history from the 16th century to the end of the 19th century and published in 1996. However, Concordia Sanchez published a book, Libraries in the Philippines, about the different types of libraries in 1973.The following recommendations are suggested: the establishment of academic archives in all educational institutions; the documentation of the history libraries and library schools including the directory of graduates and the organization of library science alumni associations; the creation of library associations' archives; librarians' awareness of the significance of their personal records; and the teaching of Philippine library history to strengthen the philosophical foundation of librarians. Other recommendations are the cooperation of librarians and school officials in giving out needed information in the writing of library history; research and publication on academic libraries, public libraries, school libraries and special libraries; information networks and library consortia; study of library publications; the role of public and private institutions in library development; and the continuing research on the development and growth of libraries and librarianship.
This study presents a more comprehensive and clearer picture and perspective on the history of libraries and librarianship in the Philippines. It also attempts to increase the knowledge of librarians and other interested parties on the development and growth of libraries and librarianship indicating the planners and stakeholders of the field.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- Philippines -- 20th century; Libraries -- Philippines -- History -- 20th century